A surface antigen expressed by a subset of neurons in the vertebrate central nervous system. - Hockfield, S (1983)
Many hypotheses for the specificity of connections in the nervous system postulate the presence of surface chemical differences between neurons. Hybridoma technology offers a potential route to identify such surface antigenic differences between neurons. Monoclonal antibody Cat-301 was one of a panel of antibodies generated by immunizing mice with homogenized adult cat spinal cord. At the light microscopic level, Cat-301 recognizes a subset of neurons in many areas of the vertebrate central nervous system. This report shows at the ultrastructural level that Cat-301 binds to a surface antigen on neurons in the intact vertebrate central nervous system. Cat-301-positive neurons carry the antigen on cell bodies and proximal dendrites but not on axons. Using secondary antibody labeled with horseradish peroxidase, we show that antibody binding sites are present along the surfaces of neurons and extend around presynaptic profiles but are excluded from the synaptic cleft. The distribution of the Cat-301 antigen at central synapses is similar to that described for some components of the extracellular matrix of the neuromuscular junction. This study demonstrates that a specific surface antigen is found on a subset of neurons and suggests that other surface markers may be present on other subsets of mammalian central nervous system neurons. Antibodies against this antigen and other surface antigens may allow insight into the mechanisms involved in the formation and maintenance of synaptic connections in the central nervous system.